Influência do tipo malha metálica e do tipo de argamassa na realcalinização eletroquímica de estruturas de concreto carbonatado - Lachovicz, Priscila Oliveira (2020)
The objective of this work was to carry out an analysis of the influence of the metallic mesh and the type of mortar on the efficiency of the electrochemical realization process. Electrochemical realcalinization is a non-destructive method performed on reinforced concrete structures that present corrosion in the reinforcement, caused by the carbonation of the concrete. When a reinforced concrete structure is affected by the carbonation phenomenon, the pH of the concrete decreases to approximately 8, while its normal values vary between 12.5 and 13.5 (basic pH). The decrease in the pH of reinforced concrete, over time, can cause damage to the passivating film between the concrete and steel, and, as a consequence, can trigger the corrosion of the reinforcement. Electrochemical realcalinization is a technique used that aims at increasing the pH of the concrete and repassivating the reinforcement. In the technique, reactions of oxygen and hydrogen occur, forming hydroxyl ions on the surface of the steel, which allows an increase in the pH and the steel’s passivation. Despite being an effective method, few studies in the area have been carried out, as it is a method in need of improvement. Therefore, in this work an analysis was carried out in the electrochemical realization process, testing other variables in the process. Therefore, specimens of 5 cm x 10 cm were used, made in two different strokes, being mortar of high performance and self-compacting, these were submitted to an accelerated carbonation camera for a period of one year and four months. After this exposure period, the carbonation depth was checked by diametrically breaking the specimens and spraying a phenolphthalein pH indicator solution. The self-compacting mortar specimens had an average carbonation depth of 3.14 mm and the highperformance specimens did not present carbonation. The technique was applied only to carbonated specimens (self-compacting), using stainless steel mesh, galvanized steel and aluminum, alkaline sodium carbonate solution, current of 1A / m² over a period of 7 days. Compressive strength, capillarity absorption and porosimetry by mercury intrusion tests were performed. Absorption and porosimetry identified an increase in the percentage of percentage in realcalinized samples and a decrease in carbonated samples, being as described in the literature. The use of stainless steel and aluminum meshes showed an increase in the pH of the samples and an increase in porosimetry in realcalinized samples, with stainless steel being the highest percentage observed, those of galvanized steel did not show an increase in pH or an increase in the percentage of porosity.